The Pemberian Edukasi Pencegahan Gagal Jantung Dalam Upaya Peningkatan Pengetahuan - Fauziansyah, Ahmad; Arifin, Mohammad Fahrul; Faqih, Moh. Ubaidillah; Karyo, Karyo (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2024)
The level of knowledge can influence whether a person takes preventive measures against the risk of disease. People with high blood pressure, diabetes, high cholesterol and obesity are at risk of developing heart failure. The risk can be prevented if the sufferer is aware and adopts a healthy lifestyle. The aim of this non-profit activity is to spread knowledge about risk factors and proactively increase the number of people affected by risk groups. The partners of this charity are residents of Semanding Village who are included in the risk group for heart failure. The methods used by the team are lectures and demonstrations, community service activities lead to increased knowledge before and after training, this is shown by seven questions that can be answered before training 2-3 and post training 5-6. It was concluded that health education provided to people at risk of heart failure will most likely increase knowledge, prevention efforts and positive attitudes of the community towards heart failure.